As luck would have it my seven ages - Jacobi, Derek 1938- (HarperCollinsPublishers, 2013)
Derek Jacobi is one of the most beloved and distinguished British theatre actors of the last fifty years. Until now, the public have known very little about the private man. In this frank, funny and moving autobiography, Derek lifts the veil for the first time on his extraordinary life, behind the footlights and beneath the theatrical make-up
Keywords: Jacobi, Derek; Jacobi, Derek -- 1938-; Actors / Great Britain / Biography; Biography; Actors; Great Britain; Großbritannien; Biografie